Comparative analysis of non-medical consumption pattern between insured and uninsured people in Ekiti State, Nigeria (2017)
Health Insurance (HI) brings about welfare improvement through improved health status and maintenance of non-medical consumption by ensuring that medical expenditures are smoothened over time. Notwithstanding, available data show that less than 4% of the Nigerian households are covered by national health insurance scheme.This implies weak ability to smoothen consumption over time whenever there is ailment. This paper aims at studying and evaluating the spillover effect of health insurance on non-medical consumption in Ekiti state. A propensity score matching estimation model was adopted to 1500 households across Ekiti state. This is the mean effect of an intervention through the mean difference in the outcomes of the treated and the control groups. The mean expenditure on non-medical consumption was N6947.03. In addition to that, the sign of the coefficient of the effect of health insurance on non-medical consumption is positive, showing that health insurance increases expenditure of insured households on non-medical consumption. Having recognized that insured households can be financially protected against unforeseen medical bill, federal government should encourage the expansion of health insurance by encouraging state government, local government and private sector to enroll their employees in health insurance programme. The paper concludes that health insurance is consumption increasing and therefore be expended to more people at local government areas to further redistribute income from the healthy to the sick.